Commercial Law - Painter, Desmond. author. aut Link
X, 154 p.
Keywords: This pack of lecturer, photocopiable, material is designed to provide sets of authentic case studies to illustrate a variety of aspects of Company Business Law. It consists of a collection of 19 individual scenarios, each of which is introduced and has a variety of tasks attached.